2006
DOI: 10.1097/01.opx.0000225103.18087.5d
|View full text |Cite
|
Sign up to set email alerts
|

Linearity Can Account for the Similarity Among Conventional, Frequency-Doubling, and Gabor-Based Perimetric Tests in the Glaucomatous Macula

Abstract: Purposes-The purposes of this study are to compare macular perimetric sensitivities for conventional size III, frequency-doubling, and Gabor stimuli in terms of Weber contrast and to provide a theoretical interpretation of the results.Methods-Twenty-two patients with glaucoma performed four perimetric tests: a conventional Swedish Interactive Threshold Algorithm (SITA) 10-2 test with Goldmann size III stimuli, two frequency-doubling tests (FDT 10-2, FDT Macula) with counterphase-modulated grating stimuli, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 22 publications
5
49
0
Order By: Relevance
“…22 This is in accord with a proposal that fixational instability in perimetry with SD ¼~0.58 can account for high variability for the size III stimulus in regions of the visual field with gradients in sensitivity 21,45 or with ''holes'' in ganglion cell arrays damaged by glaucoma. 20,26 Both of these explanations for the effect are consistent with our finding that test-retest variability may be decreased with only a modest increase in stimulus size when soft edges are used. The hard edge of the size III target means that a 0.58 displacement would stimulate responses from a completely different set of ganglion cells, so the soft edges of the blobs were designed to cause a smoother transition between responsive and not responsive ganglion cells.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…22 This is in accord with a proposal that fixational instability in perimetry with SD ¼~0.58 can account for high variability for the size III stimulus in regions of the visual field with gradients in sensitivity 21,45 or with ''holes'' in ganglion cell arrays damaged by glaucoma. 20,26 Both of these explanations for the effect are consistent with our finding that test-retest variability may be decreased with only a modest increase in stimulus size when soft edges are used. The hard edge of the size III target means that a 0.58 displacement would stimulate responses from a completely different set of ganglion cells, so the soft edges of the blobs were designed to cause a smoother transition between responsive and not responsive ganglion cells.…”
Section: Discussionsupporting
confidence: 79%
“…These results provide guidance for design of perimetric stimuli and confirm predictions of neural modeling of the pathophysiology of glaucoma. 22,26 Imaging measures can be helpful in assessing progression in patients with early stages of disease, in large part because of lower between-subject variability than found in perimetry. 44 However, once a defect has reached an average of À5 dB, imaging measures reach a floor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 However, normal between-subject and test-retest variability are high for FDP. A recent study 9 showed large, normal, between-subject variability on FDP: an MD of Ϫ5 dB was within 95% confidence limits of normal, as was a pattern standard deviation (PSD) of 5 dB (up to 8 dB in some cases).…”
mentioning
confidence: 96%